Solitary fibrous tumors/hemangiopericytomas with different variants of the NAB2-STAT6 gene fusion are characterized by specific histomorphology and distinct clinicopathological features - Barthelmeß, Sarah; Geddert, Helene; Boltze, Carsten; Moskalev, Evgeny; Bieg, Matthias; Sirbu, Horia; Brors, Benedikt; Wiemann, Stefan; Hartmann, Arndt; Agaimy, Abbas; Haller, Florian (American Journal of Pathology, 2014)
Recurrent somatic fusions of the two genes, NGFI-A-binding protein 2 (NAB2) and STAT6, located at chromosomal region 12q13, have been recently identified to be presumable tumor-initiating events in solitary fibrous tumors (SFT). Herein, we evaluated a cohort of 52 SFTs/hemangiopericytomas (HPCs) by whole-exome sequencing (one case) and multiplex RT-PCR (all 52 cases), and identified 12 different NAB2-STAT6 fusion variants in 48 cases (92%). All 52 cases showed strong and diffuse nuclear positivity for STAT6 by IHC. We categorized the fusion variants according to their potential functional effects within the predicted fusion protein and found strong correlations with relevant clinicopathological features. Tumors with the most common fusion variant, NAB2ex4-STAT6ex2/3, corresponded to classic pleuropulmonary SFTs with diffuse fibrosis and mostly benign behavior and occurred in older patients (median age, 69 years). In contrast, tumors with the second most common fusion variant, NAB2ex6-STAT6ex16/17, were found in much younger patients (median age, 47 years) and represented typical HPCs from deep soft tissue with a more aggressive phenotype and clinical behavior. In summary, these molecular genetic findings support the concept that classic pleuropulmonary SFT and deep-seated HPC are separate entities that share common features but correlate to different clinical outcome.
EVALuna2:6577